Mosquito Larvae Destroyer Using Nanopowder Synthesized from Neem Seeds - Saraswathy1, Gomathinayagam; Pappayee2, Nagappan (Asian Journal of Chemistry, 2013)
The present study explored the effects of Azadirachtin nano-powder synthesized from neem seeds on the destruction of mosquito larvae. The neem seed is subjected to extraction, vacuum distillation, evaporation and drying to obtain the Azadirachtin powder. It is reduced to nano-size by means of planetary ball milling equipment. The size 473 nm is confirmed by particle size analyzer. Lab-scale testing was done on the mosquito larvae species Culexpipiens and the larvicidal mortality was observed after 24 h of exposure with different concentrations (0.125 and 1 mg/L of Azadirachtin). At the lower concentration of 0.125 mg/L, larval mortalities are 17.39 ± 2.08 %, whereas at higher concentration of 1 mg/ L, it is 78.423 ± 2.08 %. In the control, the mortality is minor 9.6 ± 0.00 %. These results suggest that the Azadirachitinnano powder can be used as an eco-friendly mosquito larvicide.